Emotional Maturity as a Predictor of Marital Adjustment among Individuals in Early Marriage in Bener Meriah Regency - Mariyani; Zirlia Anggraini; Dinda Khairunnisa; Budiman (Psikoislamedia: Jurnal Psikologi, 2026)
The early stage of marriage is an important developmental phase, as individuals are required to adjust to new roles, responsibilities, and relational dynamics. Emotional maturity is considered a psychological factor that plays a significant role in successful self-adjustment during this period. This study aims to examine the relationship between emotional maturity and self-adjustment in the early stage of marriage. The proposed hypothesis is that there is a positive relationship between emotional maturity and self-adjustment. This research employed a quantitative approach with a correlational design. The participants were individuals in the early stage of marriage, selected using sampling techniques based on predetermined research criteria. Data were collected using emotional maturity and self-adjustment scales and analyzed using statistical correlation techniques. The results indicate a significant positive relationship between emotional maturity and self-adjustment. These findings emphasize the important role of emotional maturity in supporting successful self-adjustment during the early stage of marriage.